Cucuk sanggul monument / Ain Shuhada Azmi ... [et al.] - Azmi, Ain Shuhada; Azlan, Nur Syazwana; Mohd Noor, Nada Alya’; Halim, Atiqah (2024)
Designing public seating requires a thoughtful approach that considers both functionality and aesthetics while addressing the diverse needs of users and the specific context of the environment. The intriguing combination of natural wood materials and modern design features is found in Fusion Timber furniture. It represents the union of classic craftsmanship and contemporary design, which are aesthetically pleasing and useful. Every piece of fusion timber furniture is an artistic expression of the designer's inventiveness, which combines novel forms, textures, and finishes with the natural beauty of wood. Fusion timber furniture's capacity to inspire a sense of harmony between modernism and nature is one of its primary attributes. Fusion timber furniture embraces the clean lines and geometric shapes of contemporary design. Meanwhile, celebrating the warmth and character of wood by combining organic materials like wood into sleek, minimalist designs or bold, abstract compositions. Furthermore, fusion timber furniture requires many techniques including carving, bending, and stacking to produce dynamic and sculptural forms, showcasing the plasticity of wood as a medium. Fusion timber furniture pieces are multipurpose and artistic pieces that enhance the atmosphere of any area they occupy, whether it's a striking dining table, a sculptured lounge chair, or a simple shelving unit. overall, mixed Timber furniture offers a distinctive and alluring interpretation of modern design that pays tribute to the enduring charm of natural materials. It is a compelling mix of heritage and innovation to maintain sustainability.